Macroprudential regulation in the European Union in 1995-2014: Introducing a new data set on policy actions of a macroprudential nature - Katarzyna Budnik; Johannes Kleibl (European Central Bank (ECB), 2018)
This paper introduces a new comprehensive data set on policies of a macroprudential nature in the banking sectors of the 28 member states of the European Union (EU) between 1995 and 2014. The Macroprudential Policies Evaluation Database (MaPPED) offers a detailed overview of the "life-cycle" of policy instruments which are either genuinely macroprudential or are essentially microprudential but likely to have a significant impact on the whole banking system. It tracks events of the introduction, recalibration and termination of eleven categories and 53 subcategories of instruments. MaPPED has been based on a carefully designed questionnaire, which has been completed in cooperation with experts from national central banks and supervisory authorities of all EU member states. This paper describes the design and structure of the new data set and presents the first descriptive analysis of the use of policy measures with a macroprudential nature in the EU over the last two decades. The results indicate that there has been a remarkable variation in the use of policies of a macroprudential nature both across EU countries and over time. Moreover, the analysis provides some tentative evidence of an impact of capital buffers, lending restrictions and caps on maturity mismatches on credit to the non-financial private sector in the EU as well as of the relative ineffectiveness of sectoral risk weights in controlling credit growth.
Keywords: E50; E60; G28; 330; macroprudential policy; macroprudential instruments; financial stability; policy assessment